Association between gene polymorphisms and clinical features in idiopathic thrombocytopenic purpura patients. Issue 8 (December 2017) - Rezaeeyan, Hadi; Jaseb, Kaveh; Alghasi, Arash; Asnafi, Ali Amin; Saki, Najmaldin
Abstract : N/A: Immune thrombocytopenic purpura (ITP) is an autoimmune disease in which increased platelet destruction and thrombocytopenia are diagnostic features. In fact, the exact pathogenesis of this disease is still unknown, but genetic changes can be a potential factor in the development of ITP. In this study, the relationship between polymorphisms with platelet destruction has been studied, which leads to decreased platelet count. Relevant literature was identified by a PubMed search (2000–2016) of English language papers using the terms 'ITP', 'polymorphism, ' and 'immune system'. The majority of genetic changes (polymorphisms) occur in immune system genes, including interferon (IFN)-γ gene. These changes lead to the dysfunction of immune system and production of pathogenic antibodies against platelet surface glycoproteins such as glycoprotein IIb/IIIa, which eventually result in the destruction of platelets and increasing disease severity. In addition, IFN-γ as well as factors and cytokines involved in megakaryopoiesis, including stem cell factor and interleukin-3 (IL-3), leads to the differentiation of megakaryocytes and platelet release. Considering the fact that IFN-γ is a factor of inflammation and thrombocytopenia, coexistence of this cytokine with thrombopoietin, stem cell factor, and IL-3 results in megakaryocytes differentiation and platelet production, which can be effective to reduce disease severity and increase the platelet counts.